Adaptive sliding mode control for finite-time stability of quad-rotor UAVs with parametric uncertainties. (January 2018) - Mofid, Omid; Mobayen, Saleh
Abstract: Adaptive control methods are developed for stability and tracking control of flight systems in the presence of parametric uncertainties. This paper offers a design technique of adaptive sliding mode control (ASMC) for finite-time stabilization of unmanned aerial vehicle (UAV) systems with parametric uncertainties. Applying the Lyapunov stability concept and finite-time convergence idea, the recommended control method guarantees that the states of the quad-rotor UAV are converged to the origin with a finite-time convergence rate. Furthermore, an adaptive-tuning scheme is advised to guesstimate the unknown parameters of the quad-rotor UAV at any moment. Finally, simulation results are presented to exhibit the helpfulness of the offered technique compared to the previous methods. Highlights: Design of robust adaptive finite-time tracker with fast convergence for quad-rotor. Self-tuning finite time control combined with proportional-integral sliding surface. No requirement to the knowledge of upper bound of parametric uncertainties.